Automated drip rate monitoring and control system for intravenous fluids of varying viscosities - Justin Suarez; Allain Jessel Macas (Researcher and Lecturer Society, 2025)
Nurses play an essential role in society by advocating for health promotion, educating the public and patients on injury and sickness prevention, engaging in rehabilitation, and giving care and support. However, increasing patient loads significantly affect nurses’ available time for critical tasks, such as monitoring intravenous (IV) fluid flow. The accuracy of IV administration can also be affected by the viscosity of the infused fluid, making precise drip rate control challenging. This study aims to develop a cost-effective IV fluid monitoring and flow rate control device using a Raspberry Pi Pico microcontroller board. The device would enable nurses to monitor and control the IV drip rate accurately and easily. The accuracy of a prototype sensor for measuring drip rates in different fluids with varying viscosities is evaluated through comparison with a manual method. The results indicate that the experimental method shows good agreement and accuracy compared to the manual method, with minor biases and acceptable ranges of differences. Control charts demonstrate higher precision in the experimental method, indicating stable and consistent measurements. Overall, the findings suggest that the prototype is effective in measuring drip rates and has potential for drip rate monitoring applications. The prototype demonstrated excellent performance in handling fluids of varying viscosities, surpassing 85%. The average percentage errors were 7.5% for Sodium Chloride, 7.67% for Hetastarch, and 8.09% for fresh milk. The prototype demonstrates the ability to enhance safety and precision in IV infusions.